THE EFFECT OF HUMAN RESOURCES DEVELOPMENT ON EMPLOYEE WORK ACHIEVEMENT AT THE DEPARTMENT OF WATER RESOURCES, COPYRIGHT AND SPATIAL PLANNING GOVERNANCE OF NORTH SUMATRA PROVINCE - Zuleha - Gultom (Movere Journal, 2021)
This research is entitled "The Influence of Human Resource Development on Employee Work Performance at the Department of Water Resources, copyright and Spatial Planning of North Sumatra Province". The purpose of this study was to determine whether there was an effect of human resource development on employee performance at the Department of Water Resources, copyright and Spatial Planning, North Sumatra Province. The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 160 employees at the Department of Water Resources, Cipta Karya and Spatial Planning, North Sumatra Province, using a random sampling technique with 48 respondents. The method used in this research is descriptive quantitative method. The data analysis technique used simple linear regression analysis with the regression equation Y = 11,331 + 698 + e. The results obtained in this study showed an R2 value of 57.4% and a t-test of 7.871 so that it can be concluded that Human Resource Development has a positive and significant effect on Employee Work Performance at the Office of Water Resources, copyright and Spatial Planning of North Sumatra Province. 42.6% is influenced by other factors.